Perencanaan Ekowisata Mangrove Desa Pasar Raya Menuju Desa Wisata Mangrove - Fitri, Rahmadhani; Siti Nurhayati; Arnita, Vina; Alfiyah, Sausan (Fakultas Teknik Universitas Cenderawasih, 2023)
Mangrove ecotourism has become one of the popular destinations in nature-based tourism. Pasar Raya Village, which is surrounded by beautiful mangrove forests, has taken the initiative to develop mangrove ecotourism and turn it into a